Developing a competitive city through healthy decision-making - Gudes, Ori; Kendall, E.; Yigitcanlar, T.; Han, J.; Pathak, V. (2013)
This chapter investigates the challenges and opportunities associated with planning for a competitive city. The chapter is based on the assumption that a healthy city is a fundamental prerequisite for a competitive city. Thus, it is critical to examine the local determinants of health and factor these into any planning efforts. The main focus of the chapter is on e-health planning by utilising Web-based geographic decision support systems. The proposed novel decision support system would provide a powerful and effective platform for stakeholders to access essential data for decision-making purposes. The chapter also highlights the need for a comprehensive information framework to guide the process of planning for healthy cities. Additionally, it discusses the prospects and constraints of such an approach. In summary, this chapter outlines the potential insights of using an information science-based framework and suggests practical planning methods as part of a broader e-health approach for improving the health characteristics of competitive cities.